Measuring venous blood oxygenation in fetal brain using susceptibility‐weighted imaging. Issue 4 (4th November 2013) - Neelavalli, Jaladhar; Jella, Pavan Kumar; Krishnamurthy, Uday; Buch, Sagar; Haacke, E. Mark; Yeo, Lami; Mody, Swati; Katkuri, Yashwanth; Bahado‐Singh, Ray; Hassan, Sonia S.; Romero, Roberto; Thomason, Moriah E.
Abstract : Purpose: To evaluate fetal cerebral venous blood oxygenation, Y v, using principles of MR susceptometry. Materials and Methods: A cohort of 19 pregnant subjects, with a mean gestational age of 31.6 ± 4.7 weeks were imaged using a modified susceptibility‐weighted imaging (SWI) sequence. Data quality was first assessed for feasibility of oxygen saturation measurement, and data from five subjects (mean ± std gestational age of 33.7 ± 3.6 weeks) were then chosen for further quantitative analysis. SWI phase in the superior sagittal sinus was used to evaluate oxygen saturation using the principles of MR susceptometry. Systematic error in the measured Y v values was studied through simulations. Results: Simulations showed that the systematic error in Y v depended upon the assumed angle of the vessel, θ, relative to the main magnetic field and the error in that vessel angle δθ. For the typical vessel angle of θ = 30° encountered in the fetal data analyzed, a δθ as large as ±20° led to an absolute error, δ Y v, of less than 11%. The measured mean oxygen saturation across the five fetuses was 66% ± 9.4%. This average cerebral venous blood oxygenation value is in close agreement with values in the published literature. Conclusion: We have reported the first in vivo measurement of human fetal cerebral venous oxygen saturation using MRI.J. Magn. Reson. Imaging 2014;39:998–1006. ©2013 Wiley Periodicals, Inc .